Analisis Yuridis Penerapan Pembuktian Tidak Langsung Dalam Perkara Penetapan Harga dan Kartel Tiket Pesawat (Studi Kasus Putusan Mahkamah Agung Nomor 1811 K/Pdt.Sus-KPPU/2022): PENERAPAN BUKTI TIDAK LANGSUNG DALAM PERKARA PENETAPAN HARGA DAN KARTEL TIKET PESAWAT (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1811 K/PDT.SUS-KPPU/2022) - Arvianda, Adzradhia Nabila; Suryanti, Nyulistiowati; Afriana, Anita (Jurnal Media Justitia Nusantara, 2025)
Indirect evidence is used by the Competition Supervisory Commission to determine the existence of violations of competition law by business actors. Indirect evidence consists of communication evidence and economic evidence. The application of indirect evidence in competition cases presents a unique challenge due to the difficulty in interpreting it. This research aims to understand and examine the validity of indirect evidence used in cases related to airline price-fixing and cartels, in the case of the Supreme Court Decision Number 1811 K/Pdt.Sus-KPPU/2022. The research uses a normative juridical approach method with analytical descriptive research specifications. The research results show that the considerations in the Supreme Court's Decision regarding the existence of an implied contract among the Reported Parties, which is proven through indirect evidence, are in accordance with Law Number 5 of 1999. The validity of indirect evidence to prove violations of the competition law is equivalent to the evidence categorized as bukti petunjuk which is regulated in Article 42 of Law Number 5 of 1999.